(untitled) (GEOmedia, 2009)
GIS and neo-geography: ESRI, Bentley and Intergraph’s vision on today’s market Jack Dangermond, Ton De Vries, Richard Zambuni and Halsey Wise from ESRI, Bentley and Intergraph, three of the major GIS player in the industry, give their opinions on the GIS international market. The development of the technology can go through the economic crisis we are facing. Key words for this development will be formation, web 2.0, CAD-GIS integration and a new idea of the GIS specialist.